2013
DOI: 10.1371/journal.pone.0067554
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Human Thymic Exosomes

Abstract: Exosomes are nanosized membrane-bound vesicles that are released by various cell types and are capable of carrying proteins, lipids and RNAs which can be delivered to recipient cells. Exosomes play a role in intercellular communication and have been described to mediate immunologic information. In this article we report the first isolation and characterization of exosomes from human thymic tissue. Using electron microscopy, particle size determination, density gradient measurement, flow cytometry, proteomic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
75
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 50 publications
(55 reference statements)
3
75
0
1
Order By: Relevance
“…We have previously reported that human thymic exosomes display a protein content including TRAs, miRNA and surface markers which together indicate a thymic epithelial cell origin16. In the current study, we identify exosomes as key regulators of late stage thymocyte maturation in vitro .…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…We have previously reported that human thymic exosomes display a protein content including TRAs, miRNA and surface markers which together indicate a thymic epithelial cell origin16. In the current study, we identify exosomes as key regulators of late stage thymocyte maturation in vitro .…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, intestinal epithelial derived exosomes have been shown to mediate MHC class II-dependent immune tolerance to dietary antigens14. The presence of exosomes is established both in the murine and human thymus, but their function is less well studied1516.…”
mentioning
confidence: 99%
“…Because it has been speculated that exosomes may participate in the shuttling of TRAs from stromal cells to thymocytes or DCs (39, 40) and we and others have shown that thymic tissue is rich in exosomes (18,19), we have taken interest in the characteristics and functions of thymic exosomes. When we investigated the protein profiles of thymic exosomes from DS and control patients, the proteins in exosomes from DS patients represent a greater diversity than the proteins from control exosomes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations of DS thymic tissue have described a decrease in thymic size (13), altered thymocyte subpopulations (14), increased thymocyte depletion, markedly enlarged Hassall's corpuscles (HCs) (15), decreased thymic output (16), and a decrease in the number of AIRE + cells in the medullary region (17). The thymic tissue also produce exosomes (18,19), which are small membrane-bound vesicles that are released by various types of cells. Exosomes are important for intercellular communication and carry proteins, nucleic acids, and lipids (20).…”
mentioning
confidence: 99%
See 1 more Smart Citation